Teachers' Perceptions of Challenges and Opportunities in Teaching Christian Religious Education in Public Schools - Giawa, Hasan Nadir (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study examines the challenges and opportunities in teaching Christian Religious Education in public schools in Indonesia. Using a qualitative approach with a phenomenological design, data were collected through in-depth interviews with Christian Religious Education teachers and classroom observations. The findings reveal several key challenges, including the diversity of student religions, limited resources and facilities, and an inflexible curriculum. Despite these challenges, teachers perceive opportunities in the increased awareness of students about the importance of religion, the use of technology and media in teaching, and the inclusive approach that utilizes religious diversity in the classroom. Teachers see these challenges as opportunities for innovation in teaching, using religious diversity as a basis for teaching universal values and leveraging technology to overcome resource limitations. This research highlights the potential to enhance Christian Religious Education by fostering more relevant, interactive, and inclusive teaching practices, suggesting that overcoming existing barriers can lead to better educational outcomes.